Nilai-Nilai Perdamaian Pada Masyarakat Multikultural - Feriyanto, F. (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2018)
This article intends to describe a necessity for the presence of peace amidst the diversity of society. This diversity is now an inevitable, especially the depletion of cultural boundaries, and ethnic identity which fuses in the context of globalization. One of the potentials in this diversity is the emergence of conflicts of interest and conflicts in the name of primordial identity. The offer of a multicultural approach will recognize the potential and legitimacy of diversity and socio-cultural differences of each ethnic group. In this view both individuals and groups of various ethnicities can join the community, engage in societal cohesion without having to lose their ethnic and cultural identity, while at the same time still obtaining their rights to participate fully in various fields of community activities.